PENGARUH ADOPSI IFRS TERHADAP AUDIT DELAY PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tegangatin Tegangatin; Christine Novita Dewi (Jurnal Riset Akuntansi dan Keuangan, 2014)
This paper provides empirical evidence to answer the concern of business professional due to The Indonesian Institute of Accountants (IAI) officially stated that Indonesia would fully adopt the International Financial Reporting Standard (IFRS) in 2012. The implementation of IFRS has its various complications to companies depending the type of industry and transaction, financial report element and accounting policy options and that would be influence in delaying audit report. Therefore, this research aims to empirically test the influence of IFRS adoption towards audit delay. The methodology of this research is using regression analysis. Population used in this research is manufacturing and financial companies that are listed in Jakarta Stock Exchange (JSX) in the period of 2009-2013. From the population, selected sample based on criteria, resulted 110 samples per year or total sample of 440 companies. Through Eview, no relation is found between IFRS adoption and audit delay. This suggests that both management and auditor have been prepared well in implementing IFRS. Keywords: Audit Delay, IFRS Adoption